Optimization of the QuEChERS method for multi-residue analysis of pharmaceuticals and pesticides in aquaculture products. (15th January 2023) - Kim, Kihwan; Choi, Younghun; Mok, Sori; Moon, Hyo-Bang; Jeon, Junho
Highlights: An QuEChERS method combined with LC-HRMS analysis was optimized. The optimized analytical method was applied to determine 52 contaminants in aquaculture products. The analysis for 303 products measured 22 contaminants in the products. Fluxapyroxad and terbutryn were of major residual contaminants. Abstract: The aim of study was to optimize an QuEChERS extraction procedure for simultaneous determination of organic pollutants in aquaculture products. The QuEChERS extracts were measured using LC-HRMS. The target contaminants include 32 pesticides and 20 pharmaceuticals which have not been regulated for the products in Korea. The method was validated according to CODEX guideline (CAC/GL 71–2009). LOD and LOQ for all analytes ranged from 0.1 to 2 μg/kg and from 0.5 to 5 μg/kg, respectively. Intra-day (n = 5) and inter-day (n = 9) accuracy and precision were evaluated with the guideline. The validated method was applied to aquaculture products (n = 303). As a result, 14 pesticides and 8 pharmaceuticals were quantified. Fluxapyroxad, a fungicide frequently detected in domestic surface waters, was found with relatively higher concentration in 17 out of 23 species. It proves that a hydrophobic inland contaminant can be accumulated in the aquaculture products.